A sanabilidade de vícios referentes aos requisitos de admissibilidade dos recursos cíveis - Daher, Mariana Aguiar (2022)
The present study aims to analyze the ways to correct deficiencies that are related to the requirements for the admissibility concerning the civil appeals. In order to do so, the work sets off from an analysis on the main features of the already mentioned requirements for admissibility, and also on the traits related to the admissibility of the appeal. Furthermore, it was sought to examine the legal act to appeal under the procedural acts’ approach with the purpose of understanding the consequences brought by the practice of the act without the fulfilment of the requirements prescribed by law. In such context, the study addresses specifically the reasons and ways the mentioned deficiencies can be corrected, entering, mainly, in a evaluation about the correction clauses introduced by the Brazilian’s Civil Code of Procedure from 2015 – articles 932 and 1.029, § 3º - and also the other changes made by Codification on the appeal’s plan as way to counteract the entitled “jurisprudência defensiva” – precedents developed by the Superior Courts which aims to inhibit the judgment of the appeal. In the end, each admissibility requirement was examined with the intention of verifying if the deficiencies that may exist are able to be corrected.